Prisión preventiva como medida de última ratio en las decisiones judiciales - Ramírez Cortez, Abel Alejandro (2021)
The principle of ultima ratio constitutes a fundamental term for the penal power of the State, difficulties arise when criteria must be established that provide a material encompassing, especially considering the political pedestal that underlies this principle, since the failure to intervene criminally is of the assemblyman. Necessarily, one of the particularities of current criminal law is its representation of prima ratio, so it is imperative to investigate arguments to force when criminal law is necessary, in terms of efficiency and logic. It is common to argue, when examining the limits to the punitive power of the State, that one of the most important principles is that of ultima ratio, understood as one of the memoirs of the principle of necessity of mediation of criminal law. Essentially, it points out that criminal law must be the posthumous device that society uses to safeguard certain legal assets, as long as there are no less harmful forms of inspection "formal and informal".........